BIRDWATCHING RACE DI TAHURA NGURAH RAI BALI SEBAGAI SARANA PENDIDIKAN LINGKUNGAN UNTUK PELAJAR DAN MAHASISWA - SUDARYANTO SUDARYANTO; L. P. ESWARYANTI KUSUMA YUNI; YUNITA HARDINI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
ABSTRACT Birdwatching race was conducted on 17-19 October 2008 at Srangan Island, Lagoon BTDC Nusa Dua and Mangrove Information Centre (MIC) Tahura Ngurah Rai Bali. This activity was aimed to increase the awareness of youngsters to environment, especially bird in their habitat. This activity was also aimed to promote one kind of ecotourism namely birdwatching in Tahura Ngurah Rai Bali. One hundred students and youngsters from Java, Lombok and Bali Island participated in this activity. The activity included discourse and birdwatching race, environmental education, and discussion on environmental issues related to development ecotourism of Tahura Ngurah Rai Bali.